A cooperative game-based mechanism for allocating ancillary service costs associated with wind power integration in China. (June 2019) - Hu, Junfeng; Yan, Qingyou; Li, Xingmei; Jiang, Zhong-Zhong; Kahrl, Fredrich; Lin, Jiang; Wang, Peng
Abstract: Wind power in China is developing rapidly. However, wind power curtailment has become increasingly severe, reaching 15% in 2015. The root cause of wind power curtailment in China is that its power system has insufficient flexibility. We analyze how to achieve a reasonable allocation of ancillary service costs for wind power plants, using a cooperative game approach. The analysis shows that, while the current allocation approach in the Beijing, Tianjin, and Tangshan power grid is based only on wind feed-in tariffs, an allocation method based on both the feed-in tariff and the capacity credit of wind would be more reasonable. Highlights: China's current electricity-based ancillary service costs allocation for wind power plants is appropriate. Wind capacity credit also influences the ancillary service costs paid by wind power plants. Ancillary service costs allocated to wind power plants with high capacity credit should be reduced.